Fine-scale features on the sea surface in sar satellite imagery. Part i: Simultaneous in-situ measurements - Soloviev, A.; Maingot, C.; Fenton, J.; Matt, S.; Lehner, Susanne; Velotto, D.; Brusch, S.; Perrie, W.; Zhang, B. (European Space Agency (Special Publication) ESA SP, 2012)
This work is aimed at identifying the origin of fine-scale features on the sea surface in synthetic aperture radar (SAR) imagery with the help of in-situ measurements. We are interested in natural and artificial features starting from the horizontal scale of the upper ocean mixed layer, around 30-50 m. These features are often associated with upper ocean dynamics and can include sharp frontal interfaces, wakes of surface ships, internal wave signatures, as well as slicks of artificial and natural origin. Atmospheric processes, such as squall lines and rain cells, can also leave a prominent signature on the sea surface. We have conducted a number of studies involving in situ observations in the Straits of Florida during SAR satellite overpasses and numerical simulations (presented in a companion paper). © 2012 European Space Agency.
CRIS-Team Scopus Importer:2024-03-18